The Leadership Character of Moses in the Journey from the Red Sea to Mount Sinai: in the Application of Congregational leadership - Dadan Wahyu; Janes Sinaga; Juita Lusiana Sinambela (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The purpose of this study is to determine the strength of Moses' leadership character in leading the Israelites, and to understand and know how to lead well based on the Bible so that it can help the congregation members' spirituality. This research uses a qualitative method of literature review. Throughout the history of human life, the quality of leadership is a determining factor in the success of an organization, both in the business world and in the world of education, government, politics, health, and religion, especially Christianity. Moses in leading the Israelites was not because of the intelligence he had but by a sincere surrender to God's will. He did not walk alone, but walked according to God's will. Success in leading people is dependent on the personality of the leader not on his skills.